Thoracic epidural analgesia and immediate extubation for less than 10 kg infants undergoing living donor liver transplantation: A report of two successful cases. (5th February 2022) - Diaz, Rodrigo; Gouvêa, Glauber; Spiller, Camila Santos; Chevi, Débora; Carneiro, Fernanda Cavalcanti; Alheira, Alice; Pureza, Ana Luiza; Steinbrück, Klaus; Fernandes, Reinaldo; Neves, Douglas Bastos; Enne, Marcelo
Abstract: Background: Perioperative pain management in small infants weighing <10 kg undergoing liver transplantation is challenging. The use of TEA in this setting has not been reported, as well as its potential role to facilitate IE, ie, in the OR. Methods: We describe here the use of TEA in two small infants who had IE after a LDLT procedure. Results: TEA was successfully performed and IE was achieved in both cases. Postoperative analgesia assessment in the OR was satisfactory according to the FLACC pain scale, with scores of 2 and 3 for each patient, respectively. There were no major complications in the postoperative period, and the two children were discharged home uneventfully. Conclusions: The use of TEA and its influence on IE rate and other perioperative outcomes should be more explored in small infants undergoing LDLT.